Bone resorption marker and associated factors among postmenopausal Chinese women in senior citizen clubs in Kuala Lumpur and Selangor, Malaysia - Leiu, Kok Hong (2019)
Bone resorption is an ongoing process in the body that affects bone health status. Increased bone resorption reduces the bone mineral density (BMD) of women and lead to osteoporosis. Assessment of bone resorption using biomarkers gained attention recently due to its ability to detect bone loss earlier and more representative compare to BMD measured at only specific skeletal sites. Many of the previous studies have focused on factors that contribute to low BMD, but there were limited studies on bone resorption among postmenopausal Chinese women in Malaysia. Thus, the objective of current study was to determine the factors that contribute to bone resorption among postmenopausal Chinese women. Anthropometric indices, namely body weight, height, waist circumference and body fat percentage of the respondents were measured. Respondents were interviewed by the researcher using a questionnaire, which comprised questions on socio-demographic characteristics, smoking behaviour, physical activity, sun exposure and dietary intake. Fasting blood samples of the respondents were collected for serum 25(OH)D and serum collagen type 1 cross-linked Ctelopeptide (CTx-1) analysis. Stepwise multiple linear regression was utilised for the final analysis. There were 214 respondents from seven consented senior citizen clubs in Kuala Lumpur and Selangor participated in the current study. The mean age of the respondents was 67.2 ± 6.6 years old, with an average 16.1 ± 7.8 year of menopause. Most of the respondents were married (77.6%), attained secondary education (40.7%), retired (49.5%) with low monthly household income (44.4%). Approximately two out of five respondents (38.8%) were overweight and obese, while nearly half of them (48.6%) had abdominal obesity (waist circumference ≥ 80.0 cm). Most of the respondents (82.2%) had an unhealthy body fat percentage (≥ 32.0%). Almost all of the respondents (98.6%) were non-smokers, but one-quarter of them (24.3%) had second-hand smoke exposure either at home or work. More than half of the respondents were moderately active (58.9%) with a median sun exposure duration of 180.0 (60.0, 300.0) minutes per week. The respondents obtained a mean score of 66.9 ± 9.9 for their overall diet quality, which needs improvement. There were 33.2% and 49.5% of the respondents had deficient (<30.0 nmol/L) and inadequate (30.0 - <50.0 nmol/L) serum 25(OH)D level respectively, and their mean level of serum CTx-1 was 0.5 ± 0.2 ng/mL. In stepwise multiple linear regression, 5.9% of the variances in serum CTx-1 was explained by younger age (B = - 0.006) and being moderately active (B = 0.065) (F = 6.632, p < 0.01). In conclusion, the present study reported younger age and being moderately active contributed to higher bone resorption among postmenopausal Chinese women. Further in-depth study is needed to explain the role of physical activity in bone health among postmenopausal women in consideration of the age factor.